How Leaders of Arm's Length Agencies Respond to External Threats: A Strategic-Performative Analysis. Issue 3 (March 2022) - Howard, Cosmo
Researchers have recently shown increasing interest in how leaders of agencies respond to external threats. This article extends Katharine Dommett and Chris Skelcher's strategic-relational analysis of agency leaders' responses to exogenous threats. It focuses on the role of dramatic performances and impression management in agencies' strategic responses. Interviews with senior officials in statistical agencies in Britain and Canada were used to assess the strategic-performative model. Agencies are better able to defend their functions and autonomy when they undertake effective dramatic performances to shape external stakeholders' impressions. These findings further our understanding of the mechanisms that influence the legitimacy and autonomy of public agencies.